The Role of Public Relations in Improving the Quality of Education in Schools - Afandi, Muhammad Abdulloh; Muadin, Akhmad; Ridani, Ahmad (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
Public relations (PR) has a strategic role in supporting the improvement of education quality. As one of the indicators of education quality is the involvement of all stakeholders in the education process, this is where PR actively builds relationships with stakeholders. This research aims to explore and describe the role of PR in improving the quality of education at SD Islam Alam (SDIA) Al-Fatah Samarinda, focusing on the role of PR. This type of research is field research using a descriptive qualitative approach. Data collection techniques include interviews, observations, and documentation. The research subjects include the headmaster, PR staff, teachers, and parents. The results of the research show that PR has an important role in improving the quality of education at SDIA Al-Fatah Samarinda. The roles of PR include: (1) building a positive school image through various promotional and publication activities, (2) increasing parent and community involvement in school activities, (3) managing effective communication between the school and local government, and (4) appropriately handling crises and emerging issues. The implementation of effective PR strategies positively impacts increasing parental participation, student motivation, and community trust in the school. This research is expected to contribute insights into the role of PR in improving education quality, serving as a reference for other educational institutions in optimizing the role of PR.